2018
DOI: 10.1021/acsami.8b07103
|View full text |Cite
|
Sign up to set email alerts
|

All-Inorganic Bismuth Halide Perovskite-Like Materials A3Bi2I9 and A3Bi1.8Na0.2I8.6 (A = Rb and Cs) for Low-Voltage Switching Resistive Memory

Abstract: As silicon-based metal oxide semiconductor field effect transistors get closer to their scaling limit, the importance of resistive random-access memory devices increases due to their low power consumption, high endurance and retention performance, scalability, and fast switching speed. In the last couple of years, organic-inorganic lead halide perovskites have been used for resistive switching applications, where they outperformed conventional metal oxides in terms of large on/off ratio and low power consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 47 publications
0
86
0
Order By: Relevance
“…h) I – V curves of forming step for all‐inorganic perovskite memory devices. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Ion Migration In All‐inorganic Perovskites As Compared With mentioning
confidence: 99%
“…h) I – V curves of forming step for all‐inorganic perovskite memory devices. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Ion Migration In All‐inorganic Perovskites As Compared With mentioning
confidence: 99%
“…In the α‐CsPbI 3 phase, I − migrates along the linearly aligned PbI 6− octahedron edge, and Cs + migrates to adjacent V′ Cs sites (Figure b) . Further, in the Cs 3 Bi 2 I 9 phase (Figure c), I − migration is achieved through the 0D face‐sharing octahedrons of [Bi 2 I 9 ] 3− , and Cs + migration occurs along the adjacent V′ Cs sites . However, in the orthorhombic δ‐CsPbI 3 phase, the direction of defect migration is not uniform due to the arrangement of the square bipyramidal units of the PbI 6− octahedrons in different directions, as illustrated in Figure S9c (Supporting Information) .…”
Section: Resultsmentioning
confidence: 98%
“…As previously mentioned, Cuhadar et al found that for Rb 3 Bi 2 I 9 perovskite, when 10% Bi 3+ cations were substituted with Na + cations, the average value of V forming significantly decreased, and some of these devices were completely electroforming‐free. [ 72 ] However, even without doping, many halide perovskite memristors are also electroforming‐free, and the reasons need to be further explored. Another controversial focus is the selection of metal electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Cuhadar et al fabricated all‐inorganic lead‐free Rb 3 Bi 2 I 9 and Cs 3 Bi 2 I 9 perovskite memristors. [ 72 ] The device had a structure of Si/SiO 2 /Ti/Pt/A 3 Bi 2 I 9 /Au (A = Rb, Cs). Both devices showed instantaneous switching phenomena in the SET and RESET processes.…”
Section: Materials For Halide Perovskite Memristorsmentioning
confidence: 99%